Oral Health Knowledge and Behaviors among Adolescents with Type 1 Diabetes - Valerie A. Orlando; Lonnie R. Johnson; Anne R. Wilson; David M. Maahs; R. Paul Wadwa; Franziska K. Bishop; Fran Dong; Elaine H. Morrato (Hindawi Limited, 2010)
Early onset and more advanced periodontal disease has been reported for children with diabetes. We surveyed oral health knowledge, attitudes, and behaviors among adolescents with diabetes in order to inform potential intervention strategies. Study subjects were youth (ages 12-19 years) with type 1 diabetes (N = 90) participating in a cohort study investigating determinants of periodontal disease at a regional pediatric diabetes specialty clinic. Over 90% of the youth had been instructed on how to brush and floss and had preventive dental care in the past year. However, 44% knew that periodontal disease is associated with diabetes and 32% knew that it can start in childhood with bleeding gums. Despite being at high risk for developing periodontal disease, the mean toothbrushing frequency was once per day and 42% did not floss. Significant opportunity exists for improving periodontal disease knowledge and adoption of preventive oral hygiene behaviors in adolescents with diabetes.